Exploring school safety models adopted by selected high schools in Berea district, Lesotho - Nyapisi, Mamphula (University of the Free State, 2022)
Cases of violence in schools suggest that schools are not safe enough to promote effective teaching and learning, though schools need to be conducive and free from any form of violence. In line with the Constitution, documents such as the Child and Welfare Act and Education Act documents that govern schools, advocate for safety in schools (Kingdom of Lesotho, 2010). This study is a qualitative case study conducted within the interpretivism paradigm. The aim was to explore safety models in specific high schools in the Berea district of Lesotho. To achieve this aim, literature on models of school safety, school safety policies, measures for ensuring school safety and violence in schools were reviewed. Data was generated using document analysis, focus group and individual interviews. Five principals from five selected high schools and three teachers from each of the five high schools took part in this study. To analyse the data, invitational theory which emphasises the importance of creating friendly and inviting environment was used as a lens. This theory asserts that in the creation of a friendly environment, principles such as trust, respect, optimism, as well as intentionality play a vital role. Findings revealed that there are still cases of violence prevalent in schools some of which are perpetrated by teachers and learners. It was also observed that teachers still use corporal punishment as a way of disciplining learners and there are learners who still bully others in schools. The study recommends cooperation between teachers and police to try and improve safety in schools as well as abolishing corporal punishment which is prevalent in schools to protect learners from any form of harm. The role played by the Ministry of Education and Training to ensure safety in schools should be clarified and all documents with directives that ensure safety in schools be put into practice.
Dissertation (M.Ed.(Policy in Education))--University of the Free State, 2022
Keywords: School safety; Violence; Corporal punishment; Gender-based violence; Bullying